2009
DOI: 10.1002/er.1637
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic analysis of renewable energy source options for a district heating project

Abstract: SUMMARYWith the increased interest in exploiting renewable energy sources for district heating applications, the economic comparison of viable options has been considered as an important step in making a sound decision. In this paper, the economic performance of several energy options for a district heating system in Vancouver, British Columbia, is studied. The considered district heating system includes a 10 MW peaking/backup natural gas boiler to provide about 40% of the annual energy requirement and a 2.5 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…They observed that concerns over environmental impacts of various energy options affect the aggregate decision outcome of the stakeholders. The economic feasibility of the aforementioned four energy source options for this district heating system was studied in Ghafghazi et al (2010). The results of this study showed that in terms of cost per MWh th of produced heat, the natural gas option was the most economic one.…”
Section: Goalmentioning
confidence: 98%
“…They observed that concerns over environmental impacts of various energy options affect the aggregate decision outcome of the stakeholders. The economic feasibility of the aforementioned four energy source options for this district heating system was studied in Ghafghazi et al (2010). The results of this study showed that in terms of cost per MWh th of produced heat, the natural gas option was the most economic one.…”
Section: Goalmentioning
confidence: 98%
“…An integrated community-scale energy model (ICEM) was [28] developed for supporting renewable energy management systems planning with the consideration of changing climatic conditions. Sensitivity analysis on various inputs to the economic model was also carried out [30]. Three methods for assessing the renewable energy potential with remote sensing (RS) were proposed.…”
Section: Renewable Energy Modelsmentioning
confidence: 99%
“…District energy generally involves heating and/or cooling for more than one building, in which either hot/cold water or low pressure steam is used as the working fluid [1]. District heating/ cooling is employed to provide heat/cold and distribute it through piping systems for users.…”
Section: Introductionmentioning
confidence: 99%